Motivational Framework of Academic Scholars and Student Leaders: Comparative Analysis on Achievement and Mastery Goals - ROSARIO F. QUICHO (Indonesian Research Journal in Education |IRJE|, 2019)
This study examined the motivational framework of the academic scholars and student leaders in terms of their achievement goals, sense of self, and facilitating conditions. Respondents were 163 scholars and 85 student leaders. Utilizing the Inventory of School Motivation, Sense of Self Scale (SOS), and facilitating Conditions Questionnaire (McInerney et al., 2001), they were purposively chosen since they have different social processes, characteristics, and of different experiences. The survey questionnaire aimed to explore their motivations in pursuing their activities and to recognize their values and goals. Anchored on Personal Investment (PI) Theory (Maehr & Braskamp, 1986), this study explored the similarities and differences of the motivational characteristics of these two groups of students and how they have invest their resources, energy, time and talent. Descriptive comparative and causal - correlation were used to guide the analysis of this research. Pearson was used to determine the relationship between socio-demographic and academic related characteristics of the respondents and motivational framework, and the inter-correlation of the different components of the motivational framework. Results revealed that the two groups have multiple achievement goals. They were high in achievement goals and on mastery goals but differed in performance goals, social goals and extrinsic goals. In terms of sense of self, they have high knowledge and beliefs about oneself and moderate social support (facilitating conditions). These two groups likewise differed in adopting achievement goals, particularly in terms of mastery goals where the academic scholars scored higher in task goals than the student leaders. They also differed in performance goals, particularly in social power where the student leaders got significantly higher score than the academic scholars.